An Eco-critical Perspective on Elizabeth Gaskell’s North and South - Chen, Hung-Chih (International Journal of Language and Literary Studies, 2024)
In Elizabeth Gaskell’s novel, North and South, Margaret Hale moves from the south of England to a manufacturing town in the north, Milton. On the one hand, she learns how the manufacturer, John Thornton, manages the cotton industry which the townspeople rely on; on the other hand, she notices how the townspeople suffer from the consequences caused by the industry. Life in Milton gradually shapes her understanding of the world and leads her to develop into an independent individual. This paper starts with an exploration of the textile town, Milton, from an eco-critical perspective. While machines continue to overtake human hands, men find it difficult to keep their positions. The incompatibility between machines and human hands, and among human hands, along with the deterioration of the environment, eventually results in dysfunction and a collapse in the ecosystem. It is argued that, despite Margaret’s efforts in establishing mutual understanding and symbiotic relationships, her future and the prospect of Milton remain uncertain. The paper concludes with the evolution of Thornton and Margaret, whose transformation facilitates their adaptability and repositions their significance within the ecosystem.